Rancang Bangun Aplikasi Hybrid Pengolahan Data Anggota dan Event Pada Cabang Olahraga (Cabor) Taekwondo Kota Mataram - Royana Afwani; Sri Endang Anjarwani; Baiq Azizah Tauhida (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
Taekwondo is one of the most popular martial arts in the world. Based on the data obtained, in the Province of West Nusa Tenggara (NTB) there were 59 training sites or also called Dojang and the most were in the City of Mataram. Currently, for routine activities carried out are UKT, championships throughout the City of Mataram, championships throughout NTB, joint training in the City of Mataram, training for trainers in the City of Mataram, and regional referee training (WASDA). In participating in these activities, member data and other requirements are always checked, the process of checking is still manual so that it tends to be complicated and vulnerable to manipulation. In this study, a hybrid application of member data processing and event was designed and made on mobile-based Mataram City Taekwondo sports, as a solution to deal with the above problems. Based on the Black Box Testing System after testing, the system runs accordingly. Based on the testing using the questionnaire in getting the results of the respondents of website users that agree, strongly agree, and enough each of them is worth 55.55%, 17.77%, and 26.66%. For testing the use of mobile the results obtained from respondents that agree, strongly agree, and enough each is worth 48.88%, 17.77%, and 26.66%. Based on the test results above, it is concluded that the system can be used.